2021
DOI: 10.1017/s0022215121000876
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative outcomes of different surgical approaches to oropharyngeal squamous cell cancer: a case-matched study

Abstract: Objective To compare the post-operative outcomes of transoral laser microsurgery, lateral pharyngotomy and transmandibular surgery in oropharyngeal cancer management. Methods Records of 162 patients treated with transmandibular surgery, transoral laser microsurgery or lateral pharyngotomy were reviewed. The transoral laser microsurgery cohort was matched with the lateral pharyngotomy and transmandibular surgery cohorts for tumour stage, tumour subsite and human papilloma virus status, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The surgical procedures during which at least one TP was used are: 7 total laryngectomies, 1 case of salvage total laryngectomy in recurrence of laryngeal cancer after radiotherapy and 1 case of revision surgery in salivary fistula occurrence after total laryngectomy; 5 myringoplasties, 9 parotidectomies, 7 cases of oropharyngeal cancer resections treated with lateral pharyngotomy approach [6] and 2 cases of revision surgery in cochlear implants.…”
Section: Resultsmentioning
confidence: 99%
“…The surgical procedures during which at least one TP was used are: 7 total laryngectomies, 1 case of salvage total laryngectomy in recurrence of laryngeal cancer after radiotherapy and 1 case of revision surgery in salivary fistula occurrence after total laryngectomy; 5 myringoplasties, 9 parotidectomies, 7 cases of oropharyngeal cancer resections treated with lateral pharyngotomy approach [6] and 2 cases of revision surgery in cochlear implants.…”
Section: Resultsmentioning
confidence: 99%
“…The median mandibular approach can fully expose the oropharynx and can remove the tongue root and tumors involving the lateral wall of the oropharynx, soft palate, and other areas under direct vision. However, this approach causes great damage to normal tissue structure, postoperative reaction, long hospitalization time, high incidence of surgery-related complications, and scarring from the lower lip to the chin affecting the aesthetics [28]. Wang et al [29] used the median approach for surgical resection of 37 patients with malignant tumors of the tongue root, and after postoperative fixation with resorbable bone splints, there were no serious complications, such as misalignment of the occlusal relationship and bone nonunion; they concluded that this approach could effectively expose and completely resect the mass under direct vision, thus reducing the damage of the lingual artery and the hypoglossal nerve.…”
Section: Median Approachmentioning
confidence: 99%